Estudos epidemiológicos do mal-do-pé (Gaeumannomyces graminis (Sacc.) von Arx & Olivier var. graminis) em arroz (Oryza sativa L.) de terras altas, no estado de Goiás - Peixoto, Cecília do Nascimento (2006)
The morphological and cultural characteristics of G. graminis var. graminis isolates from rice and grasses were studied. The fungus forms two types of mycelia, dark macrohyphae that join laterally to form runner hyphae or rhizomorphs and hyaline or infectious microhyphae, as well as fan shaped hyphae characteristic of the pathogen. Pigmented and lobed hyphopodia on lower leaf sheaths were formed both under natural conditions and artificial inoculations of plants. The perithecia containing asci and ascospores were found on leaf sheaths lesions on field samples. The perithecia were produced on leaf sheaths of inoculated plants as well as on detached sterilized leaf sheaths and on culture medium, potato-dextrose-agar (PDA). Hyphae and hyphopodia were formed from germination tubes of ascospores, and the hyphae under moist stress conditions produced chlamydospores which were initially hyaline and later attained dark color. The culture of Ggg, was characterized by fluffy aerial mycelium, white in the initial stages of growth and later with age, the colony color changed from dirty-white or mouse gray to almost black. The marked diagnostic colony characteristic of whorled appearance was the curling back of marginal hyphae. The amount and time of formation of perithecia varied among the isolates tested. The virulence test conduced with 20 isolates of rice and grasses, showed differences in aggressiveness both on rice seedlings and adult plants. In general, isolates from rice were more aggressive on rice than isolates from grasses. The test with four levels of inoculum (0, 5, 1.0, 2.0, 4.0 g per plant of autoclaved sorghum grains) and two plant ages showed that 60-day old were more susceptible than 35-day old plants. The spontaneous infection of healthy plants was observed in the greenhouse indicating the role of ascospores in the dissemination of black sheath rot in rice. Furthermore, the pathogenicity of ascospores of Ggg on rice plants was confirmed by inoculations tests. Six fields of upland rice were surveyed in the advanced stages of maturation for the incidence of black sheath rot. The disease incidence on tillers, under natural conditions of infection, ranged from 68 to 100%. The pathogenicity of 20 isolates retrieved from rice and grasses were studied. All isolates were pathogenic to rice and grasses such as baranyard grass (Echinochloa crusgalli), fountain grass (Pennisetum setosum) signal grass (Brachiaria sp), crab grass (Digitaria horizontalis), plantain signal grass (Brachiaria plantaginea), indian goose grass (Eleusine indica) and southern sandbur (Cenchrus echinatus). Winter cereals such as wheat, oat, rye, barley and triticale as well as sorghum, corn, and millet exhibited different degrees of susceptibility to the isolate Ggg-a 01. Significant differences were observed in relation to characteristic symptoms on the culm, lesion height, number of tillers or dead plants, presence of characteristic mycelium, fan shaped hyphae, production of hyphopodia and perithecia. The formation of perithecia was not observed on leaf sheaths of inoculated plants of millet, sorghum, southern sandbur and maize. All inoculated wheat plants were killed indicating more susceptibility than other cereals. The resistance of 58 upland rice genotypes were tested in the greenhouse, utilizing rice isolate Ggg-a 01. Of the genotypes assessed, the lesion height of SCIA16 and SCIA08 was significantly shorter compared to the highly susceptible genotype CNAS10351. The progress and dissemination of black sheath rot in rice was studied during two years under field conditions in savanna sensu lato ‘cerrado’. The central line of each plot was inoculated with isolate of Ggg to establish the infection foci. The soil was infested with four levels of inoculum (5.0, 10.0, 20.0 and 40.0 g of autoclaved sorghum grains containing mycelium / 40 cm) and main tiller of plants (4, 8, 16 and 32, tillers per plot/ 40 cm) were inoculated with 2.0 cm-long detached leaf sheaths containing perithecia by insertion between the culm and leaf sheath of the tiller. There was no significant effect of inoculum level on the disease severity obtained by soil infestation with mycelium as well as the plants infected with perithecia. However, the total area under disease progress curve was significantly smaller for plant infection with perithecia than for soil infestation by mycelium, during 2002/2003. The evaluation of disease incidence for the analysis of gradients was based on infected tillers in 1.6 square meter area, five lines on either side of the inoculated 40 cm-long central line. The analysis according models of Gregory (1968) and Kiyosawa & Shiyomi (1972) showed the existence of gradients in the first year, both for levels of inoculum of soil infection by mycelium and plant infection with perithecia. In the second year (2004/2005), there was no well defined gradient for all the treatments. The disease progress was not affected by inoculum levels on soil or plant infections. Monomolecular model was found more adequate in tests conduced under greenhouse conditions while the models of Gompertz and monomolecular, better described the disease progress under field conditions.